Antioxidant, antimicrobial and anti-cancer properties of silver nanoparticles biosynthesized using artichoke waste extract: DOI: 10.48129/kjs.10012 - El-Chaghaby, Ghadir; Rashad, Sayed; Eid, Heba (Kuwait Journal of Science, 2022)
In the present work, a green method for biosynthesis of silver nanoparticles (AgNPs) from artichoke processing is proposed. The formation of AgNPs spectrophotometrically confirmed by appearance of maximum peak at 430 nm. Transmission electron microscope revealed AgNPs with different shapes and average particle size (88.94 nm). Phytochemical and gas chromatography results indicated the presence of important compounds especially phenols and flavonoids in artichoke waste extract. AgNPs were tested to determine their potential antioxidant, antibacterial and anticancer activities. The results showed that AgNPs have high antioxidant capacity. Antibacterial test showed that AgNPs were capable of inhibiting Staphylococcus aureus, Bacillus cereus, Escherichia coli and Salmonella. AgNPs showed anticancer activity against breast cancer cell line with a decline in cells viability with increase of AgNPs concentration and IC50 (144.29μmole/ml). Based on these results and the benefits of phytochemicals detected in artichoke waste extract, this waste could be effectively used for silver nanoparticles preparation.